Late non-infectious lung damage in children after allogeneic hematopoietic stem cells transplantation - Yu. V. Skvortsova; A. E. Rudneva; V. M. Delyagin; Yu. A. Lerkhendorf; G. V. Tereshchenko; D. N. Balashov; M. A. Maschan; A. A. Maschan (Онкогематология)
Hematopoietic stem cells transplantation (HSCT) technology currently allows curing a lot of malignant and non-malignant diseases in adults and children. However, HSCT is highly toxic treatment. HSCT complications include the possibility of prolonged immunodeficiency, alloand autoimmune reactions and various organs dysfunction. These conditions require careful monitoring by specialists, early diagnosis and appropriate treatment. This article discusses the clinical features, diagnosis and treatment options of such late complications as non-infectious lung disease. These conditions can lead to disability of patients. Relevance and importance of timely diagnosis of these pathological conditions, including the range of clinical tests available on a residence, with a view to effective treatment can improve the quality of life ofchildren with complications after HSCT. Theoretical issues are illustrated by case report.